Throat pain - N. A. Korovina (Медицинский совет, 2013)
The article describes the main causes of acute sore throat and differential diagnosis of acute pain in the throat of various etiologies. The role of viral and bacterial infections in the occurrence of acute sore throat is considered. The main groups of drugs used for the etiotropic, pathogenetic and symptomatic treatment of tonsillitis and pharyngitis are characterized; current approaches to the selection of drugs for the local treatment of the oropharynx diseases are described.